Relativsätze im Deutschen und im Italienischen: Ein Vergleich unter Berücksichtigung von Nicht-Standard-Varietäten - Murelli, Adriano (Linguistik Online, 2021)
This contribution focuses on relative constructions in German and Italian. After sketching the theoretical background, the relativization strategies attested in standard and non-standard varieties of both languages will be presented and analysed from a typological perspective. Then, an attempt will be made to understand why some of these constructions were excluded from the standard variety when both languages were codified; this can only be done by adopting a sociolinguistic perspective. Finally, the rise of a new standard variety, the so-called neo-standard, will be discussed and the relative constructions attested in it will be examined.